Effect of Low/High Temperature on Structure and Wear Resistance of Ionic Nitriding Layer on SUS301L Stainless Steel for HVAC - GUO Hong-wei, YANG Chun-fang, CUI Zhi-guang, GUO Yu (Cailiao Baohu)
In order to improve the comprehensive performance of the surface of SUS301L stainless steel used for heating, ventilation and air conditioning (HVAC), the surface nitriding was carried out to form an ionic nitriding layer at low temperature (500 ℃) and high temperature (900 ℃), and the microstructure and wear characteristic of the ionic nitriding layer were analyzed by various methods. Results showed that when nitriding at 500 ℃, an ionic nitriding layer with about 7 μm was formed on the substrate surface, accompanied with white light organization distributed flatly, and the organization only dissolved a very small ratio of N. At 900 ℃, an ionic nitriding layer with the thickness of about 23 μm was obtained on the substrate surface by nitriding treatment, and the diffraction peak corresponding to CrN and N was detected in the XRD spectrum of the ionic nitriding layer. After nitriding at 500 ℃ and 900 ℃, the hardness of the samples increased greatly. The hardness of the ionic nitriding layer prepared at 900 ℃ was the highest. Moreover, gradually increasing the load caused the decline of the hardness of the ionic nitriding layer obtained at 500 ℃. Compared with SUS301L stainless steel substrate, the friction coefficient of ionic nitriding layer was more stable, indicating that the ionic nitriding layer had better friction and wear characteristics. Besides, the depth and width of the wear mark of the ionic nitriding layer decreased obviously, and the wear amount of the sample after nitriding at 900 ℃ was higher than that of the ionic nitriding layer at 500 ℃.